The worldwide diversity of scalp seborrhoea, as daily experienced by seven human ethnic groups. (29th September 2017) - Pouradier, F.; Liu, C.; Wares, J.; Yokoyama, E.; Collaudin, C.; Panhard, S.; Saint‐Léger, D.; Loussouarn, G.
Abstract: Objective: The re‐greasing process and kinetics of the human scalp, post‐shampooing, have been previously documented, in vivo, on a few Caucasian subjects. The objective of the presented research was to extend such knowledge over seven different ethnic groups. Methods: The post‐shampooing re‐greasing kinetics of the scalp was studied on 1325 subjects (women and men of two distinct age classes) from seven different ethnic groups in their residential and native country. Sebum amounts were determined onto small shaved scalp areas at various times post‐shampooing, using the Sebumeter ® technique. Results: As previously published on Caucasian subjects, scalp re‐greasing process follows a hyperbolic‐like kinetics over days. However, amounts of collected sebum highly vary with ethnicity. As recorded through the casual level (CL) at the equilibrium phase, 2–3 days post‐shampooing, the highest amount of sebum was found in African American subjects, followed in descending order by Caucasian American, Japanese, Chinese, Thai, Caucasian European and Indian subjects, the latter showing very low values. Lower amounts of sebum were recorded in the older age class in all ethnics, as compared to the younger one, and male subjects were found higher sebum producers than women, irrespective of ethnicity. Conclusion: The kinetics and slopes of the re‐greasing process of the human scalp appear similar in all ethnic groups studied. However, striking quantitative differences are found between the seven ethnic groups, resulting from different sebaceous production levels and scalp hygiene routines. Abstract : The objective of the presented research was to extend such knowledge over seven different ethnic groups. The kinetics and slopes of the re‐greasing process of the human scalp appear similar in all ethnic groups studied. However striking quantitative differences are found between the seven ethnic groups, resulting from different sebaceous production levels and scalp hygiene routines.